Promoting sustainable development of contemporary housing estates. Gamification as an incentive methodology to support urban design - Bradecki Tomasz; Askarizad Reza; Bal Daria; Dymarska Natalia; Sanigórska Marta; Haupt Patrycja; Hetmańczyk Piotr (Miscellanea Geographica: Regional Studies on Development, 2025)
The article explores the possibilities of improving urban planning in a direction towards sustainable development and the mitigation of contemporary climate change, as well as exploring the spatial aspects of the demographic processes in built development, concentrating on residential environments. By focusing on housing estates, the authors aim to address real-world challenges in urban planning and to emphasise the applicability of theoretical concepts to practical scenarios. The discussion underscores the significance of bridging the gap between theory and practice in urban planning education for students, architects, urban planners, and developers, as well as cities' inhabitants. The authors contend that unconventional methods, such as games, can serve as valuable resources for imparting the complex concepts related to urban planning. Several internationally recognised games are scrutinised and compared for their educational qualities in the context of sustainable development.